Protective effects of 1α, 25‐Dihydroxyvitamin D3 on cultured neural cells exposed to catalytic iron. Issue 11 (1st June 2016) - Uberti, Francesca; Morsanuto, Vera; Bardelli, Claudio; Molinari, Claudio
Abstract: Recent studies have postulated a role for vitamin D and its receptor on cerebral function, and anti‐inflammatory, immunomodulatory and neuroprotective effects have been described; vitamin D can inhibit proinflammatory cytokines and nitric oxide synthesis during various neurodegenerative insults, and may be considered as a potential drug for the treatment of these disorders. In addition, iron is crucial for neuronal development and neurotransmitter production in the brain, but its accumulation as catalytic form (Fe 3+ ) impairs brain function and causes the dysregulation of iron metabolism leading to tissue damage due to the formation of toxic free radicals (ROS). This research was planned to study the role of vitamin D to prevent iron damage in neuroblastoma BE(2)M17 cells. Mechanisms involved in neurodegeneration, including cell viability, ROS production, and the most common intracellular pathways were studied. Pretreatment with calcitriol (the active form of vitamin D) reduced cellular injury induced by exposure to catalytic iron. Abstract : This research intended to study the role of vitamin D to prevent iron damage in neuroblastoma cells BE(2)M17. The mechanisms involved in neurodegeneration, such as cell viability, ROS production and the most common intracellular pathway have been studied. The pre‐treatment with vitamin D was able to reduce cellular injury induced by Fe 3+ . These data suggest the potential therapeutic use of vitamin D in new strategies to treat or prevent degenerative brain diseases.